Integration of Spiritual Values in The Hidden Curriculum to Build Akhlaqul Karimah Character - Fitriani, Siti Anisa' Nur; Wulandari , Mutiara Ayu (Generate Digital Publishing, 2024)
Objective: The objective of this study is to explore the integration of spiritual values in the hidden curriculum within educational environments, with a focus on fostering character development that aligns with Islamic principles, ultimately enhancing spiritual intelligence and noble character (akhlaqul karimah) in learners. Research Design & Methods: This study employs a qualitative approach, utilizing observation, in-depth interviews, and documentation to gather data. The research explores how the hidden curriculum influences students' spiritual and moral growth outside of the formal curriculum and the role of spiritual values in shaping character. Findings: The findings reveal that the hidden curriculum plays a significant role in students' spiritual and moral development beyond the formal curriculum. Spiritual values such as faith, piety, gratitude, and empathy are integrated into everyday experiences, guiding students to internalize moral and ethical principles. This integration fosters a supportive educational environment that encourages students to develop positive behavior, respect for others, and a sense of responsibility toward themselves and their environment. Implications & Recommendations: The study suggested that schools integrate spiritual values in educational practices, train educators to facilitate a hidden curriculum, create an environment that supports students' spiritual and social growth, and involve families and communities in character development. Contribution & Value Added: This study reveals the vital role of the hidden curriculum in fostering students' spiritual intelligence and character, emphasizing the integration of spiritual values to develop morally grounded and academically competent individuals, and provides practical guidance for educators.